PENGARUH MEDIA PEMBELAJARAN TIK TOK TERHADAP KEAKTIFAN SISWA KELAS VII PADA MATA PELAJARAN PPKn - Pandar, Moh; Sahid, M (Center for Research and Community Service (LPPM) University of Abulyatama, 2024)
The aim of this research is to find out whether the Tik Tok learning media can influence student activity in Pancasila and Citizenship Education subjects. The technique used in this research is the Nonprobability Sampling technique with the aim of taking samples that do not provide equal opportunities to members of the population, and the determination is not random. This research was conducted at SMPK Santo Yusup with a class VII sample of 30 respondents. Data collection was carried out using questionnaires. The results of data analysis used by researchers include Validity Test, Reliability Test, Normality Test, Simple Linear Regression Test and Hypothesis Test. The results of the research based on the hypothesis. The test using the T test shows that the t test value, namely the paired test table shows that the calculated T is 29.042 > T table 1.69726. So, it can be concluded that learning tik tok has a positive effect with a significant level of 0.000 < 0.05 partially on learning tik tok. So it can be said that Ha is accepted and Ho is rejected. With the intention that this tik tok learning variable influences student activity.